Argania spinosa essential oil ameliorates colonic damage and extraintestinal alterations in a rat model of acetic acid‑induced colitis by suppressing oxidative stress and inflammation (2023)
The present study was designed to elucidate the prophylactic and therapeutic potential of argan oil (AO) (from the kernels of the argan tree, Argania spinosa) against acetic acid (AA)-induced colitis and associated alterations in the liver and kidneys of rats. Colitis was induced by intra-rectal administration of 4% AA solution for 3 consecutive days. Some groups of rats were treated orally with AO (5 mL/kg) for 5 consecutive days before and after AA administration, while other groups were treated with either the vehicle or AO alone. Macroscopic and microscopic lesions in the tissues were assessed, while oxidative stress, antioxidant parameters and myeloperoxidase (MPO) activity were determined by biochemical methods. Haematological and serum chemistry parameters were also evaluated. Administration of AO before or after AA induction produced improvements in body weight gain, faecal consistency, macroscopic and histologic scores of the colonic mucosa compared to rats treated with AA alone. Furthermore, AO treatment caused significant reduction in colonic levels of hydrogen peroxide (H2O2), malondialdehyde (MDA), advanced oxidation protein products (AOPP) and serum MPO activity, while glutathione S-transferase (GST) and superoxide dismutase (SOD) activities were increased in the colon and kidneys, compared to the colitis control. Acetic acid treatment resulted in significant reduction in erythrocyte and leucocyte indices in relation to healthy controls. Taken together, treatment of rats with AO protected colonic tissues from acetic acid-induced inflammation and suggests that the oil may be considered for preventive and therapeutic purposes against inflammatory bowel diseases.